Quantitative systems modeling approaches towards model-informed drug development: Perspective through case studies - Verma, Meghna; Gall, Louis; Biasetti, Jacopo; Di Veroli, Giovanni Y.; Pichardo-Almarza, Cesar; Gibbs, Megan A.; Kimko, Holly (Frontiers in Systems Biology, 2023)
Quantitative systems pharmacology (QSP) modeling has become an increasingly popular approach impacting our understanding of disease mechanisms and helping predict patients’ treatment responses to facilitate study design or development go/no-go decisions. In this paper, we highlight the notable contributions and opportunities that QSP approaches are to offer during the drug development process by sharing three examples that have facilitated internal decisions. The barriers to successful applications and the factors that facilitate the success of the modeling approach is discussed.